The relation between Self-Esteem and Productivity: An analysis in higher education institutions - Gómez-Jorge, Fabiola; Díaz-Garrido, Eloísa (Frontiers in Psychology, 2023)
Background: Due to the importance of academic training, allowing upward socioeconomic mobility and being key to getting out of poverty, as indicated by the United Nations in its 2030 Agenda, investment in quality education is key. The objective of this paper is to analyse the impact of Self-Esteem in the work environment on Teaching and Research Productivity within the field of higher education in Spain. Method: The research is carried out among the teaching staff of the Rey Juan Carlos University of Madrid (Spain). A structured questionnaire was used to ask about Self-Esteem and Productivity. Data analysis is conducted using 272 valid questionnaires analysed with R-commander software. The validity of the variables is analysed to check the quality of the questionnaire. Linear regression analysis is used to exam the relationship between Self-Esteem and Productivity and is completed with ANOVA analysis to study the most significant differences between these variables. Results: We identified a positive correlation between Self-Esteem and Productivity, where significant differences have been observed depending on the age and seniority of the teaching staff. Conclusion: This research contributes positively to the achievement of Sustainable Development Goals 3 (Good Health and Well-being) and 4 (Quality Education), in addition to highlighting the importance of universities ensuring the Self-Esteem of their teachers, having a very positive impact on the education received by the students, on the quality and prestige of the teaching centre, and on society, increasing academic research and educational quality. Likewise, the results achieved can be extrapolated to other sectors.